Looking at the pedagogy of innovation and entrepreneurial education with Bernstein - Svanborg Rannveig Jónsdóttir 1953-; Allyson Macdonald 1952- (2011)
Innovation and entrepreneurial education (IEE) as a curriculum area was first introduced into the official curriculum in Iceland in 1999. In this article pedagogy in IEE is analysed using the concepts of classification (power) and framing (control) developed by the sociologist Basil Bernstein. When working with IEE, teachers are faced with the challenge of balancing structure and freedom and of allowing learners some control of their learning. Most teachers are accustomed to strong classification and strong framing, but IEE requires weaker forms aligned with integration and coconstruction of knowledge when appropriate. By analysing data from interviews with thirteen teachers who work with IEE and by developing indicators based on Bernstein’s concepts, it is possible to identify four modes of pedagogy. Teacher choice of instructional discourse involves personal choice and disposition. The majority of teachers working with IEE relinquishes some control of communication to learners, but find it more difficult to free themselves of strong delineation of roles. Teachers that embrace and deliberately organize their work towards some measure of learner control develop a pedagogy that supports working with IEE. Kennsla í nýsköpunar- og frumkvöðlamennt skoðuð í ljósi kenninga Bernsteins. Nýsköpunar- og frumkvöðlamennt (NFM) eða nýsköpun og hagnýting þekkingar var fyrst kynnt sem sérstakt svið í námskrá fyrir íslenska grunnskóla 1999. Í þessari grein er kennsla í NFM skilgreind út frá hugtökum félagsfræðingsins Basil Bernstein um flokkun (vald) og umgerð (stjórnun). Kennarar sem vinna með NFM þurfa að hafa hæfilegt jafnvægi milli valfrelsis og skipulags sem leyfir nemendum nokkra stjórn á námi sínu. Flestir kennarar eru vanir sterkri flokkun og stífri umgerð en vinna með NFM þarfnast minni stýringar í takt við samþættingu og sameiginlega þekkingarsköpun þegar það á við. Í þessari rannsókn voru greind viðtalsgögn frá 13 kennurum sem unnu með nýsköpunarmennt og var hugtökum Bernsteins beitt til að draga fram lýsingu á því ...